Biaxial creep study of copper on the basis of isochronous creep surfaces - Kowalewski, Z.L. (Archives of Mechanics, 1996)
A methodology for determination of isochronous creep rupture surfaces is proposed on the basis of creep investigations carried out on pure copper under complex stress state at 523 K. This procedure is also used to determine the curves of the same time to reach the minimum creep rate and curves representing the same time to tertiary creep period. Analysis of these curves shows that for the stress level taken into account as a reference point in the plane (σ11, √3 σ12), the material damage degree increases proportionally until rupture is achieved. It means practically that such isochronous curves coincide. Verification of the selected fundamental creep rupture criteria is carried out on the basis of the experimental data. It is shown that the Sdobyrev creep rupture criterion gives the most suitable tool to describe the degradation process of copper subjected to long-term constant loading conditions at elevated temperature.